Nilai Ekonomi Langsung Berbagai Sistem Pengelolaan Hutan Rakyat di Desa Mirring, Kab. Polewali, Sulawesi Barat - Daud Irundu; Andi Arafat; Rahmania Rahmania (Jurnal Hutan dan Masyarakat, 2018)
Public forests are land ownership whose management is oriented to timber productivity, but in addition to timber under stands can also be cultivated food crops and environmental services all of which have economic value. Community forest management can provide direct and indirect economic benefits as an alternative source of economic income for the people of Mirring Village, Binuang District, Polman , West Sulawesi. This research aims to find out how much the direct economic value of community forest based on its management system which can then be used as a reference for future forest management plan. The research was conducted from March to December 2017. Data were collected using survey and interview methods, where the observed variables included descriptions of community forests, community forest productivity including timber and non-timber forest products, and local market prices. The analysis is done descriptively quantitative. The result of the research shows the highest economic value is in agroforestry forest management system of Rp.127.962.157, followed by mixed stands  and monoculture system of Rp.97.894.958 and Rp.71.728.608, respectively. Products produced by community forests consist of timber and non-timber forest products.Keywords:  economic value, forest community, Polman.